Parents of Finnish Students Partnership in School Activities from an Ecological Perspective (Ecological Systems Theory): Case Study of Pop-Up School Day - Alazwari, Dina Mohammed; Almutairi, Norah Mashan (Journal of Educational and Psychological Sciences, 2021)
This study aimed to identify the motivations of students’ parents to participate with the school, and to identify the most important features of the partnership between the student’s parent and the school. And the role of the student’s guardian and the school in the partnership between them. To achieve the objectives of the study, the researchers used the case study methodology, and the study was applied to (9) parents and teachers within the Pop-Up School Day event at Yoanson Normale Kolo School in Yuanso in North Karelia Province, Finland, and an interview was conducted with them. The results of the study showed the following: a) The motives for parents’ participation with the school in Finnish experience were their keenness to build strong social relations with their children’s teachers, their desire to learn and develop oneself, a sense of responsibility towards society and a desire to provide service towards it, and the positive impact of the partnership on the personality of students. B) Parents ’partnership with the school is characterized by being an interactive partnership that brings the school out of its isolation, and it is a smart partnership based on the effective employment of parents’ experiences and the achievement of positive gains for the school. C) The company between parents and the school is characterized by the fact that it mainly seeks to develop the student’s personality, enhance the status of the teacher and support his empowerment in society. And by appreciating the effort it provides. D) The role of the parent and the school is to partner with the preparation, planning and implementation of activities. Based on the results, a set of recommendations and proposals were presented to strengthen the partnership between home and school in order to achieve complementarity in raising children and achieving the goals of both parties.